Second exam of right colon improves adenoma detection rate: Systematic review and meta-analysis of randomized controlled trials - Kamal, Faisal; Khan, Muhammad Ali; Lee-Smith, Wade; Sharma, Sachit; Acharya, Ashu; Imam, Zaid; Farooq, Umer; Hanson, John; Pulous, Vian; Aziz, Muhammad; Chandan, Saurabh; Kouanda, Abdul; Dai, Sun-Chuan; Munroe, Craig A.; Howden, Colin W. (Endoscopy International Open, 2022)
Background and study aims A second examination of the right colon, either as a second forward view (SFV) or as retroflexion (RF) in the cecum, can increase adenoma detection rate (ADR) in the right colon. In this meta-analysis, we have evaluated the role of a second examination of the right colon in improving ADR.Methods We reviewed several databases to identify randomized controlled trials that compared right colon SFV with no SFV, and RCTs that compared SFV with RF in the right colon, and reported data on ADR. Our outcomes of interest were ADR and polyp detection rate (PDR) with SFV vs no SFV, right colon and total withdrawal times, and additional ADR and PDR with SFV vs RF. For categorical variables, we calculated pooled risk ratios (RRs) with 95 % confidence intervals (CIs); for continuous variables, we calculated standardized mean difference (SMD) with 95 % CI. Data were analyzed using random effects model.Results We included six studies with 3901 patients. Comparing SFV with no SFV, right colon ADR and PDR were significantly higher in the SFV group: ADR (RR [95 % CI] 1.39 [1.22,1.58]) and PDR (RR [95 % CI] 1.47 [1.30, 1.65]). We found no significant difference in right colon withdrawal time (SMD [95 % CI] 1.54 [–0.20,3.28]) or total withdrawal time (SMD (95 % CI) 0.37 [–0.39,1.13]) with and without SFV. We found no significant difference in additional ADR between SFV and RF.Conclusions SFV of the right colon significantly increases right-sided and overall ADR.